Psychology, the motive powers : emotions, conscience, will - McCosh, James, 1811-1894 (ATLA monograph preservation program, 1888)
"In this volume, I unfold the characteristics of the motive powers, as they are called the orective, the appetent, the impulsive powers; the feelings, the sentiments, the affections, the heart, as distinguished from the Gnostic, the cognitive, the intellect, the understanding, the reason, the head. These motive powers fall under three heads: the emotions, the conscience, the will. It is not to be understood that these are unconnected with each other, or with the cognitive; emotions contain an idea which is cognitive. The conscience may be regarded as combining characteristics of each of the two grand classes; being cognitive as discerning good and evil, and motive as leading to action; the will has to use the other powers as going on to action. Emotion occupies more room than the other two in this treatise, inasmuch as its operations are more varied, and as the account usually given of it (so it appears to me) is more defective"--Introduction. (PsycINFO Database Record (c) 2010 APA, all rights reserved)